CHANGE IN THE PRODUCTION LINE FOR BETTER OPERATIONAL PERFORMANCE IN MACHINING Eucalyptus spp. WOOD - Baraldi, Lucas; Docha, Maria Cecília Mota; da Rocha, Márcio Pereira; Klitzke, Ricardo Jorge; Baraúna, Edy Eime Pereira; Robert, Renato Cesar Gonçalves (Floresta, 2024)
The present study aims to evaluate the effect of layout modification on operational efficiency, productivity, and yield in two wood machining lines for planks, beams, rafters, boards, and battens of Eucalyptus spp. Daily production data was collected from the two machining lines over a period of 21 days, before and after the layout modification. For the calculation of operational efficiency, productivity, and yield, data on raw material volume and final product was used. The average operational efficiency of line one increased by 0.1534 m³.op.h⁻¹, and line two by 0.1850 m³.op.h⁻¹ after the layout modification. The productivity of lines one and two also increased after the restructuring, with differences of 0.1364 m³.op.h⁻¹ and 0.1099 m³.op.h⁻¹, respectively. The wood machining yield did not differ between the two lines. The results indicated production homogenization and performance improvement in wood machining.